Sleep Disorders in Early Psychosis: Incidence, Severity, and Association With Clinical Symptoms. (8th September 2018) - Reeve, Sarah; Sheaves, Bryony; Freeman, Daniel
Abstract: Sleep disturbance is known to be associated with psychosis, but sleep disorders (eg, insomnia, nightmare disorder, sleep apnea) have rarely been investigated. We aimed to provide the first detailed assessment of sleep disorders and their correlates in patients with early psychosis. Sixty outpatients aged between 18 and 30 with nonaffective psychosis were assessed for sleep disorder presence, severity, and treatment using a structured diagnostic interview, sleep diaries, and actigraphy. Psychotic experiences, mood, and psychological wellbeing were also measured. Forty-eight patients (80%) had at least one sleep disorder, with insomnia and nightmare disorder being the most common. Comorbidity of sleep disorders within this group was high, with an average of 3.3 sleep disorders per patient. Over half of the sleep disorders had been discussed with a clinician but almost three-quarters had received no treatment. Treatment according to clinical guidelines was rare, occurring in only 8% of cases ( n = 13). Sleep disorders were significantly associated with increased psychotic experiences, depression, anxiety, fatigue, and lower quality of life. Sleep disorders are very common in patients with psychosis, may have wide-ranging negative effects, and merit routine assessment and treatment in psychiatric practice.